Методика оцінки показників ефективності радіоелектронного комплексу моніторингу повітряного простору - Волочій, Б. Ю.; Озірковський, Л. Д.; Шкілюк, О. П.; Мащак, А. В. (Видавництво Львівської політехніки, 2013)
In this paper a method for estimation efficiency indexes for algorithm behavior of radioelectronic complex system of airspace monitoring is developed. This method takes into account the structure of adioelectronic complex system of airspace monitoring, technical and tactical characteristics of the reliability of hardware and qualifications of the human operator. Method involves the following stages. Forming of equivalent algorithm behavior is the first stage. Equivalent algorithm behavior is composed of operating and verifying blocks which reflect the functions of the radioelectronic complex system and the actions of human operator. For equivalent algorithm behavior forming is required to add two types of operating blocks that will characterize the reliability of hardware and software. Developing structural-automatic model is the second stage. Structural-automatic model is formalized representation of structure and behavior of radioelectronic complex system. Developing of structural-automatic model involves solving the following tasks: select a set of parameters of radioelectronic complex system that must be included in its model. The components of the vector state and basic events are defined. Modificational component rules tree of the state vector based on the components of the vector state and basic events is formed. The model of the algorithm behavior radioelectronic complex system is developed as a graph and state transitions. Developing of this model is the third stage of method. This task is performed using the software module ASNA-1. The system of linear differential equations of Kolmogorov - Chapman is formed and solved by program module ASNA-1. Solution of linear differential equations is obtained in the form of probability distribution being in the states. The fourth stage provides for forming and investigation of the efficiency indexes for algorithm behavior of radioelectronic complex system of airspace monitoring based on probability distribution being in the state. This method is the further development of modeling technology of discreet-continuous stochastic systems and multiple analysis for efficiency indexes of complex information systems. The example of the application of this method for resolving tasks of the system-technical designing radioelectronic complex sytem of airspace monitoring is represented. Розроблено методику оцінки показників ефективності алгоритму поведінки радіоелектронного комплексу моніторингу повітряного простору з урахуванням його структури, техніко-тактичних характеристик, показників надійності апаратних засобів та кваліфікації людини-оператора. Розроблена методика є подальшим розвитком технології моделювання та проведення багатоваріантного аналізу показників ефективності складних інформаційних систем.
Method of estimation of indexed of efficiency of the radio electronic complex system monitoring of air space
Keywords: radio electronic complex system of airspace monitoring; algorithm of the functional behavior; mathematical model of the algorithm behavior; method of development behavior models; радіоелектронний комплекс моніторингу повітряного простору; алгоритм функціональної поведінки; математична модель алгоритму поведінки; методика побудови моделей поведінки